STRATEGY OF SALAF EDUCATION TO MAINTAIN TRADITION IN THE ERA OF MODERNIZATION (Case Study of Nurul Qadim Islamic Boarding School) - Iman, Dian Zulfatul; Qamariah, Qamariah; Khoiro, Ummul; Hani, Ummi; Juwita, Juwita; Mudarris, Badrul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This paper is based on Nurul Qadim Islamic Boarding School Paiton Probolinggo which has integrated salaf education and modern education. This Islamic boarding school combines yellow book-based education with the national curriculum and optimizes technology to improve the learning process. This study aims to analyze the efforts of Islamic boarding schools in maintaining the tradition of salaf education and adapting to the development of the times. The focus of this study is how this Islamic boarding school maintains traditional methods such as bandongan, sorogan, and memorizing yellow books, while integrating the national curriculum and technology. The research method used is a qualitative approach with case studies, through observation and analysis of Islamic boarding school curriculum documents. The results of this study indicate that Nurul Qadim Islamic Boarding School has succeeded in balancing religious traditions and the demands of modernity, making it an adaptive education model. This Islamic boarding school not only produces students who master religious knowledge, but are also ready to face global challenges with skills that are relevant in the modern era.